The impact of exchange rate volatility on trade: The evidence from Russia - Irina Tarasenko (Voprosy Ekonomiki, 2021)
This paper analyzes the effects of exchange rate volatility on exports and imports of a range of goods between Russia and its 70 trading partners from 2004 until 2018. The goods in question fall into eight product categories, as follows: (i) agricultural raw materials; (ii) chemicals; (iii) food; (iv) fuels; (v) manufactured goods; (vi) ores and metals; (vii) textiles; and (viii) machinery and transport equipment. Exchange rate volatility is measured using the standard deviation of the first difference in the logarithmic daily nominal exchange rate. The paper concludes that exchange rate volatility had a negative impact on exports of agricultural raw materials, manufactured goods, and machinery and transport equipment. In contrast, it was found to have a positive and significant impact on trade in fuels and imports of chemicals and textiles.